Integrated single cell and bulk sequencing analysis identifies tumor reactive CXCR6+ CD8 T cells as a predictor of immune infiltration and immunotherapy outcomes in hepatocellular carcinoma - Li, Xiaogang; Gao, Zheng; Chen, Jiafeng; Feng, Shanru; Luo, Xuanming; Shi, Yinghong; Tang, Zheng; Liu, Weiren; Zhang, Xin; Huang, Ao; Gao, Qiang; Ke, Aiwu; et al. (Frontiers in Oncology, 2023)
Background Various immune cell types in tumor microenvironment (TME) of hepatocellular carcinoma (HCC) are identified as important parameters associated with prognosis and responsiveness to immunotherapy. However, it remains incompletely understood how various factors could influence immune cell infiltration. Hence, we investigated single cell multi-omics landscape of immune infiltration in HCC, in particular key gene and cellular subsets that shape immune infiltration, might bridging immunotherapy response and immune cell infiltration. Methods We grouped HCC patients based on immune cell infiltration score calculated by single sample gene set enrichment analysis (ssGSEA). Differential expression analysis, functional enrichment, clinical traits association, gene mutation analysis, tumor immune dysfunction and exclusion (TIDE), prognostic model construction were utilized to investigate the multi-omics immune infiltration landscape. Stepwise regression were further used to identify key genes regulating immune infiltration. Single cell analysis was used to explore expression pattern of candidate genes and dissect associated cellular populations. Immunohistochemistry and multiplexed fluorescence staining were used to further validated our results. Results we group HCC patients into high and low immune infiltration clusters. Mutations of CTNNB1 and TTN are significantly related to immune infiltration and could alter the enriched cell populations in TME. TIDE analysis demonstrated that T cell dysfunction and T cell exclusion score were enriched in high and low infiltration group, respectively. Six risk genes and five risk immune cell types were identified and were used to construct risk scores and nomogram model. CXCR6 and LTA identified by stepwise regression were highly associated with immune infiltration. Single cell analysis revealed that LTA was mainly expressed in tumor infiltrated T lymphocytes and partial B lymphocytes, while CXCR6 was predominantly enriched in T and NK cells. Notably, CXCR6+ CD8 T cells are characterized as tumor enriched, which were potential predictor for high immune infiltration, immune-checkpoint blockade (ICB) response and therapeutic target, confirmed by ROC analysis and immunotherapy cohort. Conclusion In summary, we provided a comprehensive single cell multi-omics landscape of immune infiltration in HCC and delineated key genes and cellular populations regulating immune infiltration, might providing insights into how the immune infiltration might be formed and therapeutically controlled in the future.